Ijazah Sanad Al-Quran: Isu Dan Permasalahannya Serta Metode Qurra' Dalam Mendepaninya - Norazman Alias; Khairul Anuar Mohamad; Samer Najeh Abdullah Samarh; Adnan Mohamed Yusoff; Ahmad Kamel Mohamed; Zulhilmi Mohamed Nor; Ahmad Sanusi Azmi (Usuli Faqih Research Centre PLT, 2024)
Non-Indexed Publication